How AI drives innovation in cardiovascular medicine - Cerrato, Paul L.; Halamka, John D. (Frontiers in Cardiovascular Medicine, 2024)
Mmedicine is entering a new era in which artificial intelligence (AI)and deep learning have a measurable impact on patient care. This impact is especially evident in cardiovascular medicine. While the purpose of this short opinion paper is not to provide an in-depth review of the many applications of AI in cardiovascular medicine, we summarize some of the important advances that have taken place in this domain.